Punk, gender and ageing : just typical girls? - Way, Laura (Emerald Publishing Limited, 2020)
Using in-depth interviews with punk women growing old disgracefully, Way explores how women construct punk identities. Reflecting on punk 'then' and 'now', they reveal the constraints punk women experience on their identities growing older, the complex relationship between appearance and dress, and the impact of social expectations around aging.